Implementasi Otokoreksi Ejaan Bahasa Indonesia pada Kamus Istilah Elektronika - Wibowo, Hilal Aji; Wibawanto, Hari (Edu Komputika Journal, 2016)
A dictionary now is available online or offline , text search resulted in the process of search is long because the database on the server is online .While application offline there are still several application a little use the feature search without text correction and auto correction text.With this software "Kamus Istilah Elektronika" will apply features autocorrection with algorithm levenshtein distance in search of text .The purpose of this study is to find how to implement features autocorrection and algorithms levenshtein distance on the application "Kamus Istilah Elektronika". Method of development application use waterfall method , consisting of 5 part those definition needs , design software and system , the implementation , testing and operation and maintenance . Testing application "Kamus Istilah Elektronika" use testing black box , : testing to the autocorrection , testing to the provision of advice with levenshtein distance . The results of research on testing features autocorrection is appearing to every word put and on algorithm levenshtein distance advice that will appear corresponding to the input. Features autocorrection implemented on the application "Kamus Istilah Elektronika" by adding the feature in box search edittext , and algorithm levenshtein distance implemented at the button search .